Cornes and Lupton's design liability in the construction industry - Lupton, Sarah (London : Wiley Blackwell, 2013)
Although other books cover a wide range of aspects of construction liability, this book draws together all the elements that relate specifically to design. It covers build procurement, two stage tendering and partnering arrangements, technical innovations in construction, and much more.
The industry context -- Liability under contract -- Law of tort: Part 1 -- Law of tort: Part 2 -- Liability under statute -- Nature of liability for professional negligence -- Fitness for purpose liability -- Duty to warn -- Duties in detail -- Liability to third parties: 'novation' and collateral warranties -- Damages -- Limitation -- Measures for limiting liability -- Standard forms of contract -- Standard forms of appointment -- Professional indemnity insurance -- Design liability in the EU -- Design liability in other jurisdictions.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed October 10, 2013).
Keywords: Architects -- Malpractice -- Great Britain; Engineers -- Malpractice -- Great Britain; Construction contracts -- Great Britain; Architects -- Malpractice; Construction contracts; Engineers -- Malpractice; LAW / Administrative Law & Regulatory Practice; Great Britain; Electronic books; Electronic books